ANALISIS EFEKTIFITAS PENDAMPINGAN ORANG TUA TERHADAP PELAKSANAAN IBADAH SEKOLAH MINGGU SECARA ONLINE DI MASA PANDEMI COVID 19 (STUDI DI GMIT NAZARET OESAPA TIMUR) - Hermin; Yulius Musa Natonis (Ra'ah: Journal of Sociology of Religion, 2021)
The role of parents is very much needed for online school worship during the Covid-19 pandemic, which is not only providing education to children who still cannot understand the pandemic that is endemic to almost the entire world including the service area of ?? the East Nazareth Oesapa GMIT Congregation. The purpose of this study was to determine the effectiveness of the role of parents in implementing online Sunday school worship during the Covid 19 pandemic which is focused on children aged 5-8 years. This research method is to use phenomenological qualitative methods, data obtained through observation and interviews, the population and samples of this study are parents who have children aged 5-8 years at GMIT Nazareth Oesapa Timur. The result of this research is that online worship is a new model in Christian worship so that it takes time to make adjustments so that online worship can be carried out wisely, online Sunday school worship is very effective in being implemented, but that does not mean church worship is ineffective. Online Sunday school is considered to be able to improve the quality of children's worship, which can be seen from adherence to worship times, serenity during worship, and the seriousness of participating in all liturgical sessions of worship, the role of parents in providing motivation to children during Sunday school worship and after Sunday school worship. online, the consequence of the implementation of Sunday school worship online is that a load of internet data pulses is getting bigger so that wise steps are needed by parents to overcome this obstacle while not sacrificing the spiritual needs of children and current assignments. the implementation of online Sunday school worship is intended to hone children's abilities towards Sunday school learning.